PERKEMBANGAN HUKUM PIDANA DALAM PENAGGULANGAN KEJAHATAN PEDOFILIA (Studi Komparasi Di Berbagai Negara Asing) - Reimon Supusepa (Faculty of Law, Universitas Pattimura, 2011)
People with pedophilia or pedofilis, making the children as the target. A pedofilis, generally perform actions, just because her desire motivation by satisfy his sexual fantasies that the crime of pedophilia is an ongoing threat to social order in society.